Las características sociodemográficas y su relación con la creación de negocios en el departamento de Loreto durante el periodo 2019 - Ruiz Reátegui, Isaías (2023)
The Loreto region is considered one of the regions where the level of entrepreneurship creation faces a large set of important challenges, including unequal opportunities and gender gaps. For the year 2018, it was found that 8 out of 10 individuals from Loreto have informal jobs, and although there are approximately 33,000 MIMYPES in the area, only 12% are considered formal jobs, Ministry of Labor (2019). The research work tries to cover the lack of information and studies on the importance of sociodemographic factors in the creation of businesses in the department of Loreto. In this sense, we find that the sociodemographic characteristics of a person influence the possibility of creating their own company in the department of Loreto, during the period 2019. Therefore, the specific sociodemographic factors that determine the entrepreneurial process are: family dynamics (specifically whether he is the head of the household or not), the level of education, the level of income, employability, work experience, and the gender of the individuals.